Evaluating indicators of oxidative stress and their relationship with Insulin Resistance in polycystic ovary syndrome - Alipour, Beitolah; Roohelhami, Elham; Rashidkhani, Bahram; Shahrdami, Farzaneh; Edalati, Sara (Progress in Nutrition, 2019)
Background: Polycystic ovary syndrome (PCOS) is the most frequent female disorder in the reproductive years. It is characterized by amenorrhea or oligomenorrhea, hyperandrogenism and obesity. Due to the unknown pathophysiology of PCOS and contradictory results of multiple studies on oxidative stress and relationship between oxidative stress and insulin resistance (IR), we aimed to evaluate indicators of oxidative stress and their relationship with insulin resistance in women with polycystic ovary syndrome. Method: This case-control study was accomplished over 90 patients diagnosed with PCOS from the Moheb Yas comprehensive Women hospital in Tehran (March-November 2015) based on the Rotterdam criteria. Additionally, 90 healthy individuals were recruited and matched according to age and BMI by simple sampling. At the beginning of the study, weight, height, waist circumference (WC), hip circumference (HC), fasting blood sugar (FBS), fasting insulin, total antioxidant capacity (TAC), malondialdehyde (MDA) were measured by standard methods. In addition, body mass index (BMI) and insulin resistance (IR) were calculated. Results: Insulin and IR were statistically higher in the PCOS group in comparison to the control group (p<0.001, p<0.001) In contrast, TAC was statistically lower in the PCOS group in comparison to the control group (p<0.001). However, there were no statistically significant differences for FBS and MDA between the two groups. Additionally, Insulin and IR had a significant positive correlation with anthropometric variables. Conclusion: According to the results obtained from this study, imbalance of oxidative status/antioxidant defenses in PCOS patients indicate that oxidative stress is probably significant in the pathogens of PCOS. Thus, recommending patients to use abundant sources of anti-oxidants may be efficient in ameliorating symptoms of PCOS.